3D freeform printing of silk fibroin. (15th April 2018) - Rodriguez, Maria J.; Dixon, Thomas A.; Cohen, Eliad; Huang, Wenwen; Omenetto, Fiorenzo G.; Kaplan, David L.
Graphical abstract: Abstract: Freeform fabrication has emerged as a key direction in printing biologically-relevant materials and structures. With this emerging technology, complex structures with microscale resolution can be created in arbitrary geometries and without the limitations found in traditional bottom-up or top-down additive manufacturing methods. Recent advances in freeform printing have used the physical properties of microparticle-based granular gels as a medium for the submerged extrusion of bioinks. However, most of these techniques require post-processing or crosslinking for the removal of the printed structures (Miller et al., 2015; Jin et al., 2016) [1, 2] . In this communication, we introduce a novel method for the one-step gelation of silk fibroin within a suspension of synthetic nanoclay (Laponite) and polyethylene glycol (PEG). Silk fibroin has been used as a biopolymer for bioprinting in several contexts, but chemical or enzymatic additives or bulking agents are needed to stabilize 3D structures. Our method requires no post-processing of printed structures and allows for in situ physical crosslinking of pure aqueous silk fibroin into arbitrary geometries produced through freeform 3D printing. Statement of Significance: 3D bioprinting has emerged as a technology that can produce biologically relevant structures in defined geometries with microscale resolution. Techniques for fabrication of free-standing structures by printing into granular gel media has been demonstrated previously, however, these methods require crosslinking agents and post-processing steps on printed structures. Our method utilizes one-step gelation of silk fibroin within a suspension of synthetic nanoclay (Laponite), with no need for additional crosslinking compounds or post processing of the material. This new method allows for in situ physical crosslinking of pure aqueous silk fibroin into defined geometries produced through freeform 3D printing.